Review paperUltrastructural alterations of human cortical capillary basement membrane in human brain oedema - Castejón, Orlando José (Folia Neuropathologica, 2014)
The capillary basement membranes are examined in severe traumatic brain injuries, vascular malformation, congenital hydrocephalus and brain tumours. They exhibit homogeneous and nodular thickening, vacuolization, rarefaction, reduplication, and deposition of collagen fibers. Their average thickness varied according to the aetiology and severity of brain oedema. In moderate brain oedema the thickness ranged from 71.97 to 191.90 nm in width, and in patients with severe brain oedema it varied from 206.66 to 404.22 nm. The basement membrane complex appears apparently intact in moderate oedema, and shows glio-basal dissociation in severe oedema. In areas of highly increased cerebro-vascular permeability, the basement membrane shows matrix disorganization, reduplication, and bifurcations protruding toward the endothelial cells, and acting as abluminal transcapillary channels. In regions of total brain necrosis, its structural stability is lost showing loosening, dissolution and rupture. Basement membrane swelling is due to overhydration of its protein-complex glycoprotein matrix. The thickening, rarefaction and vacuolization are induced by the increased vacuolar and vesicular transendothelial transport. The degenerated basement membrane areas exhibit a finely granular precipitate interpreted as protein, proteoglycan, glycoprotein, and agrin degraded matrix.